The functions of questions in the classroom discourse / Jun Nirlawati Mohd Sahidol - Mohd Sahidol, Jun Nirlawati (2012)
This study identified and analysed the functions of questions in BEL 120 classroom discourse in Universiti Teknologi MARA Pahang (UiTM). Thus, the data for the study mainly consisted of the audio tape recording transcriptions of five BEL 120 lecturers that were conveniently selected from July - November 2010 session. Altogether, a total of 20 hours of audio recordings were transcribed from these five lecturers selected. Each lecturer was recorded twice during the session. The data from the audio recording transcriptions were analysed based on the framework set for the investigation; the functions of questions, the types of questions and speech act. The questions found were analysed and categorized into nine different function adapted from Athanasiadou (1990), Tsui (1992), Gabrielatos (1997) and Thompson (1998) namely seek information, guidance and awareness raising, class management, feedback and checking, evoke students’ response, seek agreement and confirmation, introduce information, stimulating thought and unclassifiable. The functions were then treated to simple frequency counts. The analysis shows that out of the functions of questions listed to be analysed, most of the questions fall under the category of evoking students’ response function and seeking information. The functions of questions that seemed to be the least common used by the lecturers were introduce information and guidance and awareness-raising. The findings of this study have raised some legitimate concerns that BEL 120 lecturers did not use a lot of questions in the classroom. Some recommendations are put forward as a guide for future improvement towards enhancing the use of questions and various functions of questions in the classroom.